O direito sucessório dos companheiros e a inconstitucionalidade do art. 1790 do Código Civil: reflexões sobre o posicionamento adotado pelo STF - Keller, Fabiana Teixeira Albuquerque (2018)
The work aims at studying the Common Law Marriage and Intestate Succession. An analysis is made of the concept of family and family entities recognized by the Federal Constitution, especially marriage and stable union. With regard to the stable union, a study was carried out on its evolution in the legislative, doctrinal and jurisprudential fields until its recognition, by the Federal Constitution of 1988, as a family entity, as well as its regulation through Laws n. 8,971 / 94 and n. 9.278 / 96 and the Civil Code of 2002. The core of the work was to analyze the succession effects among the companions, resulting from the existence of a stable union, mainly in relation to succession competition with descendants, ascendants and collateral, after the judgment of the Resources Extraordinary no. 878,694 and no. 646,721 / RS, where the STF recognized and declared the unconstitutionality of art. 1,790 of the Civil Code of 2002, equating the stable union with marriage with regard to inheritance rights. Due to this STF positioning, the partner has the same rights as the spouse in the legitimate succession, which brings them closer to the marriage family. In the